Obesity With Hypertension Events In Taccorong Village, Bulukumba District - Wiwi Yuniarti; Muriyati; Hamdana (Comprehensive Health Care, 2019)
According to the world health organization 2015, says that hypertension is one of the main causes of premature death throughout and hypertension kills nearly 8 billion people every year in the world. Obesity is one of the risk factors for hypertension, because of the accumulation of fat in the body, the higher a person's body mass index, the higher the risk of developing hypertension. The purpose of this study is to know the relationship between obesity and the incidence of hypertension in the village of Taccorong caused Bulukumba district in 2018. The population in this study was the obese community in Taccorong village, Bulukumba regency, a population of 68 respondents, a sampling technique used by a purposive sampling technique. This type of research is analytic research with a cross-sectional approach. The test used for the relationship of obesity with the incidence of hypertension in Taccorong village Bulukumba district in 2018. Is the Pearson Chi-Square test, with the results of the study that obese respondents who experienced grade 1 hypertension were 18 respondents (85.7%) and obesity 1 respondents who had hypertension grade 2 were 3 respondents (14.3%). While the obese 2 respondents who experienced grade 1 hypertension were 6 respondents (31.6%) and obesity 2 respondents who experienced grade 2 hypertension as many as 13 respondents (68.4%). Based on the test results obtained values (p=0.000) then Ho is rejected and Ha is accepted. The conclusion of this study is that there is a correlation between obesity and the incidence of hypertension in Taccorong village, Bulukumba district in 2018. It is recommended for the Puskesmas Bonto Nyeleng Institution to pay attention to its working area to detect total obesity.